Surface electromyographic measurements on land prior to and after 90 min of submersion (swimming) are highly reliable - Olstad, B. H.; Zinner, C.; Cabri, J; Kjendlie, P.-L. (Journal of Electromyography and Kinesiology, 2014)
The purpose of this study was to investigate the reliability of surface electromyography (sEMG) measurements after submersion (swimming) for 90 min. Isometric maximal voluntary contractions (MVC) on land and in water were collected from eight muscles on the right side of the body in 12 healthy participants (6 women and 6 men). Repeated measures analyses of variance (general linear model ANOVA) showed no significant differences in the peak amplitude MVC scores between land pre and post measurements for all muscles, p > .05. The mean of the Intraclass correlation coefficient (1, 1) for land pre and land post was .985 with (95% Cl = .978-.990), for land pre and water pre .976 (95% Cl = .964-.984) and for land pre and post, water pre and post .981 (95% Cl = .974-.987). Measuring sEMG on land before and after a prolonged submersion is highly reliable without additional waterproofing when using electrodes with 57 mm diameter.